Consistent estimation of the fixed effects ordered logit model - Baetschmann, Gregori; Staub, Kevin E.; Winkelmann, Rainer (Journal of the Royal Statistical Society. Series A, Statistics in society, 2015)
The paper considers panel data methods for estimating ordered logit models with individual-specific correlated unobserved heterogeneity. We show that a popular approach is inconsistent, whereas some consistent and efficient estimators are available, including minimum distance and generalized method-of-moment estimators. A Monte Carlo study reveals the good properties of an alternative estimator that has not been considered in econometric applications before, is simple to implement and almost as efficient. An illustrative application based on data from the German Socio-Economic Panel confirms the large negative effect of unemployment on life satisfaction that has been found in the previous literature.